2020
DOI: 10.1002/jhet.3932
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new fungicide by screening triazole sulfonylhydrazone derivatives and its downy mildew inhibition in cucumber

Abstract: Downy mildew is a very important detrimental disease that lead reduced to fruits and vegetables. Due to the continuous growth of drug resistance, finding novel fungicides with dissimilar modes of function from present fungicides for controlling downy mildew are imminent. This work is an extension of our preceding research on the original triazole sulfonamide derivatives lead compound. Triazole sulfonamide as a remarkable nitrogen-containing heterocyclic compound opposed cucumber downy mildew (CDM) develops a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Honda et al (2009) determined the sensitivity of Phytophthora infestans to amisulbrom, and the results suggested that this fungicide can significantly inhibit the release of zoospores at 0.1 μg/mL. 18 Fontaine et al (2019) and Li et al (2020) reported that amisulbrom has good field control effects for Plasmopara viticola and Pseudoperonospora cubensis and has great application prospects in the control of oomycete diseases. 19,20 Our previous study on amisulbrom activity demonstrated that it exhibits excellent inhibitory activity and control potential against P. litchii.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Honda et al (2009) determined the sensitivity of Phytophthora infestans to amisulbrom, and the results suggested that this fungicide can significantly inhibit the release of zoospores at 0.1 μg/mL. 18 Fontaine et al (2019) and Li et al (2020) reported that amisulbrom has good field control effects for Plasmopara viticola and Pseudoperonospora cubensis and has great application prospects in the control of oomycete diseases. 19,20 Our previous study on amisulbrom activity demonstrated that it exhibits excellent inhibitory activity and control potential against P. litchii.…”
Section: Introductionmentioning
confidence: 99%
“…18 Fontaine et al (2019) and Li et al (2020) reported that amisulbrom has good field control effects for Plasmopara viticola and Pseudoperonospora cubensis and has great application prospects in the control of oomycete diseases. 19,20 Our previous study on amisulbrom activity demonstrated that it exhibits excellent inhibitory activity and control potential against P. litchii. However, the resistance risk and resistance mechanism of P. litchii to amisulbrom have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…1 Cucumber downy mildew (CDM) caused by Pseudoperonospora cubensis is one ofthemostseverecucurbitdiseases.Ifnotcontrolledintime,itmaylead to a 50% loss in annual cucumber production. [2][3][4][5] The fungicide control of CDM is among the most effective methods for managing the disease worldwide. However, for cucurbit cultivators who rely heavily on fungicide use, the re-emergence of Pseudoperonospora cubensis along with the failure of previously effective host resistance and the reduced sensitivity of pathogens to several fungicides has emerged as a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Cucumber downy mildew (CDM) caused by Pseudoperonospora cubensis is one of the most severe cucurbit diseases. If not controlled in time, it may lead to a 50% loss in annual cucumber production 2–5 . The fungicide control of CDM is among the most effective methods for managing the disease worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…As an important nitrogen-containing compounds in organic synthesis, sulfonyl hydrazones are widely employed to construct C–C, C–N, and C–S bonds. Compounds with sulfonyl hydrazone structural units present various biological activities, including antifungal [ 19 , 20 , 21 ], antibacterial [ 22 , 23 ], anticancer [ 24 , 25 , 26 ], and insecticidal [ 27 ] activity. However, there are no reports on the synthesis and bioactivity evaluation of thiochromanone derivatives containing a sulfonyl hydrazone structure.…”
Section: Introductionmentioning
confidence: 99%